Sound waves of classical music optimize the performance of hydroponic lettuce cultivation - Valdiviezo-Gonzales, Lorgio (2024)
It is proposed to evaluate the impact of the application of musical sound waves on the development of lettuce crops through domestic hydroponics. For this purpose, an experimental method was applied to 36 units of common lettuce crops, half were exposed to classical music with 70 dB and the other half were exposed to environmental noise. Subsequently, the size, weight and growth time of the crop were measured. The results recorded that the exposure of lettuce to classical music achieved greater development (growth of 31.90 cm) at 30 days, unlike lettuces with exposure to environmental noise (growth of 29.90 cm) at 38 days. Likewise, the weight of the cultures exposed to classical music exceeded those of the cultures exposed to environmental noise by 98.34 g. Sound waves generated a positive effect on the development of lettuce crops. In this sense, it is recommended to apply sound waves to other types of crops to determine the most appropriate frequency for the maximum development of each crop.